The impact of drinking attitude on alcohol-related problems in the Asian workplace. - Chong, Li Wei. (2012)
Alcohol use is strongly influenced by culture. The amount of alcohol consumed, the manifestation and prevalence of alcohol problems in a society depend on its attitude towards drinking. Multiple cross-cultural studies have documented that Asian students drink less than their Western counterparts. Also, societies with a temperance culture appear to have more alcohol-related problems than non-temperance culture, even though the latter consume less alcohol. These alcohol problems bring a heavy cost burden to the economy and society. They include liver diseases, alcohol use disorders and absenteeism and productivity loss in the workplace. With regards to alcohol-related workplace problems such as absenteeism, the working environment in Japan and China will be examined to reflect the impact of drinking attitude on these problems.